The Creation and Assessment of the Herbal Face Pack - Nupur Nandkishor Chaudhari; Sunila .A. Patil; Rupesh Manilal Chaudhari; Nikita Bharat Chaudhari; Pushpraj Jagannath Chaudhari (Recent Trends in Cosmetics, 2024)
The aim of this study is to develop and test herbal facials for glowing skin using organic herbs. Natural herbal components in the form of dry powder, such as Orange peel, Tulsi (Holy Basil), Masoor dal (Lentin), Multani mitti (Calcium Bentonite), and Methi (Fenugreek), Sandalwood (Santalum album) were bought from the local market. Orange peel powder was made via commercial shade drying. To guarantee a consistent composition, all powdered natural materials were weighed exactly, sieved through #120 mesh, and geometrically combined. The powder was then evaluated for morphological, physicochemical, physical, phytochemical, and irritancy factors in addition to stability testing. Consequently, in this project, we used simple materials to make vegetable masks that are easy to use. Following assessment, it found that the face packs had two positive attributes: they did not cause skin irritation and maintained their consistency even when stored in stable conditions. The study's conclusions offered empirical support for the claim that a herbal face pack may significantly brighten skin. Owing to the positive effects the entire study had on participants, product claims might be supported by it.
Keywords: Formulation; Herbal face pack; Natural herbal; Skin; evaluation